The “Puppet-Body” in Japanese Theater - Do Valle, Scarlett Siqueira (2022)
This article aims to discuss artistic research and discovery on the “puppet-body.” This text contains notes and questions extracted from the author's work diary from the activities of her Study Group. In 2019, this Group, linked to the Master’s Degree of the Escola Superior de Artes Célia Helena (ESCH-SP) examined the resignification of the body of the actor in body-puppet form mainly from the Ningy? buri style of Kabuki, inspired by the Bunraku and the filmed stage show Tambours sur la digue (Drums on the Dam) of the Théâtre du Soleil. In conceptual terms, our work took from Meyerhold, Oida, Kusano, and Greiner.